Glassy Metals - Russew, Krassimir; Stojanova, Liljana (Springer Berlin Heidelberg : Imprint: Springer, 2016)
The topics discussed in this book focus on fundamental problems concerning the structural relaxation of amorphous metallic alloys, above all the possibility of studying it on the basis of viscous flow behavior and its relation to rheological anomalies, such as bend stress relaxation, thermal expansion, specific heat, density changes, and crystallization. Most relaxation studies deal with the relaxation changes of a single definite material property, and not with a wider spectrum of physical properties integrated into a common framework. This book shows that it is possible to describe these property changes on the basis of a more comprehensive theoretical understanding of their mechanism.